(Nie)konflikt wiary z niewiarą we wspólnocie na przykładzie myśli Jeana Vaniera – założyciela wspólnoty niepełnosprawnych L’Arche (Przegląd Religioznawczy – The Religious Studies Review, 2020)
Jean Vanier, who founded the L’Arche community in France for over 50 years, relied heavily on the foundation of Christian thought and realistic philosophy, which is firmly built on Aristotelianism and Thomism. It is hard not to notice that Vanier often refers in his books and other publications or statements to Christian roots. At the same time, in the books about the community (mainly “The community is a place of joy and forgiveness”), he indicates that in the communities of the Ark there is a place for both believers and non-believers. On the intellectual level, it is difficult not to notice the conflict between inclusiveness (the invitation to be in the community is directed to everyone) and exclusivity (the foundations of the community, its spiritual heart are Christian and Catholic roots). In my article, I would like to highlight three main elements: a brief introduction on Vanier’s understanding of community; the importance of the Christian religion in building a community; an attempt to reconcile faith with unbelief in community in Vanier’s view.